Impact of Sugarcane Cultivation on Benthic Macroinvertebrate Communities in Tropical Streams - Marcus Vinícius França; Erika Mayumi Shimabukuro; Welber Senteio Smith; Mariana Morilla; Ricardo Hideo Taniwaki (Limnological Review)
Tropical streams host diverse benthic macroinvertebrates, essential for ecological processes and bioindicators of ecosystem health. However, land use changes, such as sugarcane cultivation, negatively impact stream structure and function. This study examined these effects by comparing streams in sugarcane-dominated areas with those in native vegetation. Streams with native vegetation showed 2226 individuals across 107 taxa, 39 families, and 52 genera, with Chironomidae (Chironominae, Tanypodinae), Leptoceridae, Leptophlebiidae, and Calamoceratidae being the most abundant. In contrast, sugarcane streams showed 692 individuals from 47 taxa, 24 families, and 19 genera, with Chironomidae (Chironominae, Tanypodinae), Dryopidae, and Simuliidae dominating. The first hypothesis suggested that sugarcane plantations reduce taxonomic and functional diversity. The results partially confirmed this, showing lower abundance and richness in sugarcane streams, though functionality remained unchanged. The second hypothesis proposed greater seasonal taxonomic variation in sugarcane streams due to hydrological differences. Results supported this, revealing stronger seasonal shifts, particularly during the rainy season. These findings highlight the significant impact of sugarcane cultivation on aquatic ecosystems. Continuous monitoring of macroinvertebrates in agricultural landscapes is crucial for assessing environmental impacts and guiding conservation strategies.